Características ecográficas abdominales del Otorongo (Panthera onca) en cautiverio - Grandez R., Ricardo (2024)
The abdomen of apparently healthy jaguars (Panthera onca) kept in confinement at the Parque de Las Leyendas Zoo (Lima) and the San Juan Zoocriadero (Pucallpa, Peru) was evaluated by ultrasound. The work included the examination of 13 specimens, young and mature, female and male. The specimens were anesthetized with a combination of Dexmedetomidine and Ketamine, and Atipamezole was used as an antidote. The Esaote MyLabOne™ equipment and the 4-9 MHz microconvex transducer were used. The anatomical location, echotexture and architecture of the abdominal organs were evaluated. From the study it was possible to conclude that the ultrasound characteristics of the abdominal organs of Panthera onca specimens are similar to those described for other species of South American wild felines, varying in length, width or thickness in correspondence to the larger size of the jaguar; and that the characteristics of the abdominal organs do not differ significantly from those described for companion animals.